Epidemiology of cutaneous leishmaniasis in central Amazonia: A comparison of sex-biased incidence among rural settlers and field biologists - Soares, Letícia; Abad-Franch, Fernando; Ferraz, Gonçalo (Tropical Medicine and International Health, 2014)
Objective: Cutaneous leishmaniasis (CL) is more frequently reported in men than in women; this may be due to male-biased exposure to CL vectors, female-biased resistance against the disease or both. We sought to determine whether gender-specific exposure to vector habitats explains male-biased CL incidence in two human populations of central Amazonia. Methods: We compared the CL incidence in one population of field researchers (N = 166), with similar exposure for males and females, and one population of rural settlers (N = 646), where exposure is overall male-biased. We used a combination of questionnaires and clinical data to quantify CL cases, and modelled disease incidence in a Bayesian framework. Results: There was a moderately higher incidence of CL among men than among women in both populations, but male bias decreased as exposure time increased. Disease incidence was overall higher among field researchers, suggesting that they are an important but understudied CL risk group. Conclusion: Our comparison of two contrasting populations provided epidemiological evidence that CL incidence can be male-biased even when exposure is comparable in both sexes. © 2014 John Wiley & Sons Ltd.
Keywords: Bayesian Analysis; Comparative Study; Disease Incidence; Disease Vector; Epidemiology; Fly; Gender Issue; Leishmaniasis; Questionnaire Survey; Rural Area; Adult; Brasil; Controlled Study; Environmental Exposure; Female; Gender Bias; Human; Incidence; Major Clinical Study; Male; Morbidity; Prediction; Prevalence; Questionnaires; Risk Factor; Rural Area; Self Report; Skin Leishmaniasis; Amazonia; Analyse Bayésienne; Análisis Bayesiano; Bayesian Analysis; Environmental Exposure; Exposición Ambiental; Exposition À L'environnement; Leishmania (viannia) Guyanensis; Phlebotominae; Phlébotomie; Adolescent; Adult; Animal; Bayes Theorem; Ecosystem; Environmental Exposure; Female; Humans; Incidence; Leishmaniasis, Cutaneous; Male; Questionnaires; Research Personnel; Rivers; Rural Population; Sex Factors; South America; Young Adult